Eucalyptus grandis plantations in Argentina in the context of sustainable silviculture - Graciano, Corina (2007)
Eucalyptus plantations represent an important forest area in NE Argentina, with 140 000 hectares covered with Eucalyptus grandis (Hill ex Maiden). Plantations in this area have high mean annual increments (30-40 m³.ha-1año-1) and high total productivity (220-370 Mg. ha-1) although they are established on sandy soils. These soils have low organic matter and nutrients contents. Therefore, it is important to analyze if the present high productivity can be sustained along rotations. Sustainability implies to maintain both productivity and nutrient status. Knowledge ofnutrients fluxes and nutrient use efficiency is a key issue to understand the way in which plantations use mineral resources in order to evaluate and select the best management practices to sustain productivity. In this chapter, productivity and nutrient cycling of Eucalyptus grandis plantations are analyzed through chronosequences established on sandy soils. The point of view adopted consider that the concept of sustainable silviculture has to be applied and that it has effects on long term forest management. Therefore, nutrient content and nutrient export in different sites and ages are analyzed, as well as litterfall decomposition. These data allow for us to estimate the system yield stability, considering the economic dimension of sustainability. Results highlight that it is necessary to manage the export of nutrients with harvest, tending to their conservation. Although the soils where E. grandis plantations are established have low natural fertility, productivity is high comparing with other regions of similar clime. Thus, nutrient use efficiency and biomass production in the studied sites are high. The highest N demand occurs 3 to 4 years after planting, whereas the highest P demand occurs 6 to 8 years after planting. Shorter rotations increase export of nutrients due to harvest. Harvest residues contain a high amount of nutrients, so their incorporation to the soil after harvest can be a good practice to maintain system nutrients pools. Nutrient stability analysis in different harvest scenarios and rotation ages show that N and Ca are the most critics nutrients in this productive system, while P and K are the more stable nutrients. To compensate nutrient losses it is necessary to apply fertilizers, specially N and P. Applications should take into account soil type and the risk of water deficit.